A step-by-step guide to starting an effective mentoring program - Cohen, Norman H. (HRD Press, 2000)
Annotation
Title from title screen
Keywords: Mentoring in business; Mentorat dans les affaires; BUSINESS & ECONOMICS; Mentoring & Coaching; BUSINESS & ECONOMICS; Training